Technology Adoption of Utility Mobile Applications across Generational Cohorts Using UTAUT: A PLS-SEM Approach - Isce Kustiawan; Maria Apsari Sugiat (Science and Technology Research Centre Universitas PGRI Semarang, 2026)
This study examines the determinants of users’ intention to adopt the PLN Mobile application among Generations X, Y, and Z in East Nusa Tenggara, Indonesia, by extending the Technology Acceptance Model (TAM) with additional constructs, including perceived value, perceived trust, perceived security, attractiveness of alternatives, and social influence, with generational cohort as a moderating variable. A quantitative causal design was applied, collecting data from 438 PLN customers using proportional stratified sampling across four regional offices. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results revealed that perceived ease of use (β = 0.322, p < 0.001), social influence (β = 0.268, p < 0.001), and perceived security (β = 0.194, p < 0.01) had significant positive effects on intention to use, while perceived value, perceived trust, and perceived usefulness were not significant predictors. Social influence also significantly influenced perceived trust (β = 0.531, p < 0.001). Moderation analysis indicated that Generation Y exhibited the strongest moderating effects across most relationships, whereas Generation Z had the least impact. These findings provide actionable insights for public digital service providers, emphasizing the need to enhance ease of use, strengthen security, and leverage peer influence to improve adoption across generational segments.